2019
DOI: 10.1111/bjop.12384
|View full text |Cite
|
Sign up to set email alerts
|

The role of visuo‐spatial abilities in environment learning from maps and navigation over the adult lifespan

Abstract: Visuo-spatial abilities have an important role in environment learning. The aim of the present study was to explore whether these abilities relate to spatial recall after learning an environment from a map or a video, and irrespective of the learner's age (from youth to old age). The study involved 431 participants from 25 to 84 years old, who were assessed for their visuo-spatial working memory, object-based mental rotation, and perspectivetaking abilities. Then, they learned environments from a map and a vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 70 publications
(132 reference statements)
10
26
0
1
Order By: Relevance
“…Arrows indicate a significant predictive relationship of the visuospatial task on the navigation task abilities predicting survey knowledge in the first-person and dynamic map perspectives, there are also relations that are specific to the perspective conditions. In both perspective conditions, visuospatial working memory contributed to performance on configurational knowledge of the environment, in accordance with studies that studied the role of visuospatial working memory in static map study and direct navigation designs (Coluccia et al, 2007;Garden et al, 2002;Muffato et al, 2020;Wen et al, 2011). Furthermore, perspective-taking ability predicted performance on the orientation tasks in both perspective learning conditions.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Arrows indicate a significant predictive relationship of the visuospatial task on the navigation task abilities predicting survey knowledge in the first-person and dynamic map perspectives, there are also relations that are specific to the perspective conditions. In both perspective conditions, visuospatial working memory contributed to performance on configurational knowledge of the environment, in accordance with studies that studied the role of visuospatial working memory in static map study and direct navigation designs (Coluccia et al, 2007;Garden et al, 2002;Muffato et al, 2020;Wen et al, 2011). Furthermore, perspective-taking ability predicted performance on the orientation tasks in both perspective learning conditions.…”
Section: Discussionsupporting
confidence: 85%
“…Although spatial information can be obtained from different perspectives, the emerging mental representations of space go beyond the modality of the learning perspective. Many studies have shown that navigators are able to draw maps of the environment after learning a route from a first-person perspective (Chrastil & Warren, 2012;Coluccia, Bosco, & Brandimonte, 2007;Kozhevnikov, Motes, Rasch, & Blajenkova, 2006;Muffato, Meneghetti, & De Beni, 2020). Additionally, navigators are able to find shortcuts and use place strategies after learning an environment from a first-person perspective, demonstrating configurational knowledge of an environment (Labate, Pazzaglia, & Hegarty, 2014;Wiener, de Condappa, Harris, & Wolbers, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Among the various cognitive abilities, research has focused mainly on visuospatial working memory (VSWM), which retains and processes visuospatial information (Logie, 1995), and perspective-taking, which is a higher-order ability to adopt different views (Hegarty and Waller, 2004). Both are needed for navigation over the adult lifespan and are liable to age-related decline (Muffato et al, 2019b). Self-reported wayfinding inclinations-e.g., an individual's self-rated sense of direction, pleasure in exploring places, and spatial anxiety (finding spatial demands worrying), which are not susceptible to change over time-have also been found positively related to environmental learning across the lifespan (e.g., Meneghetti et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive abilities can be expected to have a role in the task requiring a switch from egocentric to allocentric knowledge (the sketch map task). This aspect is newly explored, however, considering not only VSWM and perspective-taking ability (found to influence navigation, Muffato et al, 2019b), but also general cognitive level. The latter is measured on a continuum from low to high, considering MoCA scores from 22 to 30 (and using the cutoffs adopted by O'Malley et al, 2018) as predictors of navigation performance after accounting for the role of age from young-old to old age.…”
Section: Introductionmentioning
confidence: 99%
“…These tests are known to be good predictors of general navigation skills and their decline with age may account in part for older adults’ deficient navigation performance (Zhong and Moffat, 2016). Notably, perspective-taking, mental rotation, and spatial memory are important abilities for spatial learning and for the dynamic manipulation of sensory information during navigation (Allen et al, 1996; Kozhevnikov et al, 2006; Meneghetti et al, 2018; Muffato et al, 2020).…”
Section: Discussionmentioning
confidence: 99%